Sustaining Poverty Gains: A Vulnerability Map to Guide Social Policy - Oscar Barriga Cabanillas; Thomas Bossuroy; Paul Andres Corral Rodas; Carlos Rodriguez Castelan; Emmanuel Skoufias (Institute of Labor Economics (IZA), 2024)
Poverty maps are a useful tool for the targeting of social programs on areas with high concentrations of poverty. However, a static focus on poverty ignores the temporal dimension of poverty. Thus, current nonpoor households still face substantial welfare volatility and are at risk of becoming poor in the face of shocks. We combine the methods of poverty mapping and vulnerability estimation to create highly disaggregated vulnerability maps. The maps include predictions of the share of chronically poor households (poverty-induced vulnerability) - the focus of traditional poverty maps - and the share of households showing a significant probability of falling into poverty (risk-induced vulnerability). As an application of the method, we estimate a vulnerability map Senegal that provides quotas for the expansion of the social registry. Accounting for the poor and the population at risk of poverty implies, in practice, the expansion of coverage into urban and periurban areas that tend to experience lower poverty rates. Also, the inclusion of nonpoor households serves as a first step toward supporting a dynamic social registry.
Keywords: C15; R11; I32; 330; poverty; vulnerability; poverty maps; targeting; social protection